Rate of Total Hip Replacement after Legg Calve Perthes Disease in a Canadian Province - Jonathan Tan; Anirudh Sharma; Rohit Bansal; Qier Tan; Heather J. Prior; Sheila McRae; James R. McCammon (MDPI AG, 2023)
Legg Calve Perthes disease is a pediatric hip condition that leads to early hip degeneration. The efficacy of operative and nonoperative treatment is not well defined in the literature. Using the rate of total hip arthroplasty as a surrogate measure for symptomatic hip degeneration, the rate of total hip arthroplasty was compared in Legg Calve Perthes disease patients with and without previous surgical intervention in the province of Manitoba, Canada. A retrospective review was conducted using de-identified, individual-level administrative records of health services for the entire population of Manitoba. Codes for Legg Calve Perthes disease, femoral osteotomies, pelvic osteotomies, adductor tenotomies, and total hip arthroplasty were searched from 1984 to 2018. The rate of total hip arthroplasty in patients with Legg Calve Perthes disease was determined for two groups: (1) patients with earlier surgical intervention and (2) patients with no previous surgical intervention. Of the 202 patients included in the study, 180 had no prior surgery and 22 had prior surgery. The rate of total hip arthroplasty between the previous operative and nonoperative groups was found to be 32% and 40%, respectively (p = 0.458). There was no significant difference in rates of total hip arthroplasty in the operative and nonoperative groups. Further prospective studies are required to elucidate the differences in outcomes between operative and nonoperative treatment groups in patients with Legg Calve Perthes disease.